The protein encoded by the human proto-oncogene c-myc. - Ramsay, G (1984)
The proto-oncogene c-myc may play a role in controlling the growth and division of normal cells, and abnormalities of the gene have been implicated in the genesis of a substantial variety of human tumors. To facilitate further study of these issues, we developed antisera that permit the identification and isolation of the protein encoded by the human and other mammalian versions of c-myc. We found that c-myc(human) gives rise to at least two phosphoproteins with apparent molecular weights of 62,000 [pp62c-myc(human), the major product] and 66,000 [pp66c-myc(human), produced in smaller quantities and possibly a modified version of the Mr 62,000 protein]. Both proteins have relatively short half-lives of approximately equal to 30 min. Mouse c-myc encodes similar proteins with molecular weights of 64,000 and 66,000. The use of cells transformed by DNA-mediated gene transfer sustained previous deductions that the entire coding domain of c-myc(human) is contained in the second and third exons of the gene and resolved previous ambiguities by showing that analogous exons specify the entire protein product of c-myc(chicken). Tumor cells containing amplification of c-myc(human) produce relatively large amounts of pp62/pp66c-myc(human). By contrast, translocations of c-myc found in cells derived from Burkitt lymphoma appear merely to sustain expression of c-myc(human) at levels found also in nontumorigenic lymphoblastoid cells, rather than to increase expression of the gene to manifestly abnormal levels.